ISOLATED PRIMARY HYDATID DISEASE OF THE BREAST - Shahid, Ayesha; Shahneela Manzoor,; Mirza, Aazma (Journal of Ayub Medical College Abbottabad, 2022)
Our study is relevant because our report adds further light on diagnosing and treating the isolated primary hydatid cyst disease of the breast. The purpose of this case report is to educate physicians and health care workers to keep this condition in the differential diagnosis of the breast lump even though the breast is a rare site of primary hydatid disease even in the endemic areas. Awareness of this entity can help in arriving at a pre-operative diagnosis, even without cytological examination, which is important in the management of the cyst. This is the first of its kind case being reported from Pakistan. Keywords: hydatid; breast; liver; echinococcus